Wt1 dictates the fate of fetal and adult Leydig cells during development in the mouse testis - Wen, Qing (Am J Physiol Endocrinol Metab, 2014)
Wilms' tumor 1 (Wt1) is a tumor suppressor gene encoding ∼24 zinc finger transcription factors. In the mammalian testis, Wt1 is expressed mostly by Sertoli cells (SCs) involved in testis development, spermatogenesis, and adult Leydig cell (ALC) steroidogenesis. Global knockout (KO) of Wt1 is lethal in mice due to defects in embryogenesis. Herein, we showed that Wt1 is involved in regulating fetal Leydig cell (FLC) degeneration and ALC differentiation during testicular development. Using Wt1(−/flox);Amh-Cre mice that specifically deleted Wt1 in the SC vs. age-matched wild-type (WT) controls, FLC-like-clusters were found in Wt1-deficient testes that remained mitotically active from postnatal day 1 (P1) to P56, and no ALC was detected at these ages. Leydig cells in mutant adult testes displayed morphological features of FLC. Also, FLC-like cells in adult mutant testes had reduced expression in ALC-associated genes Ptgds, Sult1e1, Vcam1, Hsd11b1, Hsd3b6, and Hsd17b3 but high expression of FLC-associated genes Thbs2 and Hsd3b1. Whereas serum LH and testosterone level in mutant mice were not different from controls, intratesticular testosterone level was significantly reduced. Deletion of Wt1 gene also perturbed the expression of steroidogenic enzymes Star, P450c17, Hsd3b6, Hsd3b1, Hsd17b1, and Hsd17b3. FLCs in adult mutant testes failed to convert androstenedione to testosterone due to a lack of Hsd17b3, and this defect was rescued by coculturing with fetal SCs. In summary, FLC-like cells in mutant testes are putative FLCs that remain mitotically active in adult mice, illustrating that Wt1 dictates the fate of FLC and ALC during postnatal testis development.